Investigation of the time characteristics of the transition of field emission to a vacuum arc; Soviet Physics. Doklady; Vol. 15 - Kartsev G. K.; Mesyats G. A. Gennady Andreyevich; Proskurovsky D. I.; Rotshtein V. P.; Fursey G. N. (1970, 1970)
В фонде НТБ ТПУ отсутствует